Synthesis, Characterization, and Low Temperature Sintering of Nanostructured BaWO4 for Optical and LTCC Applications - S. Vidya; Sam Solomon; J. K. Thomas (Advances in Condensed Matter Physics)
Synthesis of nano-BaWO4 by a modified combustion technique and its suitability for various applications are reported. The structure and phase purity of the sample analyzed by X-ray diffraction, Fourier transform Raman, and infrared spectroscopy show that the sample is phase pure with tetragonal structure. The particle size from the transmission electron microscopy is 22 nm. The basic optical properties and optical constants of the nano BaWO4 are studied using UV-visible absorption spectroscopy which showed that the material is a wide band gap semiconductor with band gap of 4.1 eV. The sample shows poor transmittance in ultraviolet region while maximum in visible-near infrared regions. The photoluminescence spectra show intense emission in blue region. The sample is sintered at low temperature of 810°C, without any sintering aid. Surface morphology of the sample is analyzed by scanning electron microscopy. The dielectric constant and loss factor measured at 5 MHz are 9 and 1.56×10-3. The temperature coefficient of dielectric constant is −22 ppm/°C. The experimental results obtained in the present work claim the potential use of nano BaWO4 as UV filters, transparent films for window layers on solar cells, antireflection coatings, scintillators, detectors, and for LTCC applications.